CHALLENGES AND ISSUES IN USING ICT IN THE ELT PROCESS - Iroda Mirzaeva (Galaxy International Interdisciplinary Research Journal, 2022)
In recent years, information and communication technology has grown in significance. Almost every aspect of life now involves the use of computers, and the Internet has grown to be a substantial source of knowledge. Because of this, it is impossible to envision education today without technology. It is clear that incorporating ICT in language lessons presents difficulties for teachers. Obviously, it takes a lot of effort and time to learn how to use it effectively.